Pentingnya Penyesuaian Kurikulum Untuk Anak Berkebutuhan Khusus Disekolah Dasar - Yessi Gusmiati; Serli Septi Munawaroh; Ika Nadia; Opi Andriani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The research approach uses descriptive qualitative using the case study method. Data collection is done through observation, interviews and document analysis. The results of the study are based on data analysis and observations in the field, namely: The First, Curriculum planning and learning of inclusive education begins with making syllabus, lesson plans, and PPI.. Second, Organizing the curriculum and learning of inclusive education starts with grouping and dividing the tasks for the implementers of curriculum and learning plans, Third, the implementation of the curriculum and learning of inclusive education in children with special needs has a special service program for each student's suitability according to the RPP and PPI that has been prepared. Fourth, Curriculum evaluation and learning of inclusive education is carried out by providing a review of the ongoing implementation process and the results of assessments of the curriculum and student learning.